CLINOSTOMUM MARGINATUM (BRAUN, 1899) AND AUSTRODIPLOSTOMUM COMPACTUM (LUTZ, 1928) METACERCARIAE WITH ZOONOTIC POTENCIAL ON PYGOCENTRUS NATTERERI (KNER, 1858) (CHARACIFORMES: SERRASALMIDAE) FROM CENTRAL AMAZON, BRAZIL - Mota Morais, Aprigio (2011)
The present study investigated the presence of helminths in fillets of red piranha, Pygocentrus nattereri (Kner, 1858), with a note of a possible zoonotic potential of its consumption in nature. We examined 40 fish caught in lakes in the floodplain of the Solimões River, located in the municipalities of Coari and Manaus in central Amazonia, Brazil. All fish examined were adults and had yellow cysts in the musculature. Of the 69 cysts found, 66 were identified as metacercariae of Clinostomum marginatum (Braun, 1899) and 3 as Austrodiplostomum compactum (Lutz, 1928). The analysis shows a higher susceptibility of P. nattereri for metacercariae of C. marginatum. The fact that metacercariae were found in fillets of P. nattereri, suggests a risk situation, addresses a concern about its use in raw form. It should not be consumed without proper inspection, processing and freezing, since ceviche, is readily consumed, mainly in the border region of the upper and Western Amazonia.